The Relation Between Firm Growth and Q with Multiple Capital Goods: Theory and Evidence from Panel Data on Japanese Firms - Hayashi, Fumio; Inoue, Tohru (Econometrica, 1991)
Fumio Hayashi, Tohru Inoue, The Relation Between Firm Growth and Q with Multiple Capital Goods: Theory and Evidence from Panel Data on Japanese Firms, Econometrica, Vol. 59, No. 3 (May, 1991), pp. 731-753